1977
DOI: 10.1007/bf00021058
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance response of Midge Larvae (Chironomus Tentans) to sediments containing heavy metals

Abstract: Avoidance reactions of chironomid larvae to contaminated sediment taken from a heavy metal impacted lake were studied . Heavy metal levels in the test sediment ranged from background of o .6 parts per million (ppm) cadmium, 77 ppm zinc and 17 ppm chromium to a maximum of 1,029 ppm cadmium, 17,262 ppm zinc and 2,106 ppm chromium . A linear relationship was established between cadmium and zinc levels in the sediment and avoidance by chironomids .An approximate threshold avoidance of metals in the sediment was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 5 publications
0
17
2
2
Order By: Relevance
“…Wentsel et al (1977a) demonstrated that metals had an impact on benthic communities in Palestine Lake. Laboratory studies have also demonstrated that metals can reduce populations of aquatic invertebrates eaten by fish (Biesinger & Christensen 1972, Clubb et al 1975, and Wentsel et al 1977b, 1977c.…”
Section: Resultsmentioning
confidence: 99%
“…Wentsel et al (1977a) demonstrated that metals had an impact on benthic communities in Palestine Lake. Laboratory studies have also demonstrated that metals can reduce populations of aquatic invertebrates eaten by fish (Biesinger & Christensen 1972, Clubb et al 1975, and Wentsel et al 1977b, 1977c.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been found that the chironomids actively avoid sediments with high levels (Wentsel et al, 1977b) ; thus they may migrate from highly contaminated areas in order to mature .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have indicated a remarkable tolerance of the worms to high concentrations of zinc, for instance, in the sediments (Funk et al, 1973, In Chapman et al, 1980 and of cadmium, zinc and chromium (Wentsel et al, 1977) at concentration levels where chironomid larvae were largely eliminated or physiologically disturbed. Among recent comprehensive studies on the relative tolerances of selected aquatic oligochaetes to heavy metals should be added those by Chapman et al (1982a and1982b).…”
Section: Lake Vnernmentioning
confidence: 99%
“…) found a particularly high incidence of characteristically deformed chironomid larvae of the genera Micropsectra, Chironomus and Tanytarsus within the same areas of Lake VAnern in which the deformed oligochaetes described below were found. Wentsel et al (1977) have shown that chironomid larvae avoid sediments contaminated with heavy metals. Populations of larvae inhabiting such sediments undergo characteristic changes in reproduction and growth.…”
Section: Introductionmentioning
confidence: 99%